ANALISIS BULLWHIP EFFECT PADA CV. XYZ - Rahargyansyah, Alief Yoga; Herlina, Herlina (Universitas Majalengka, 2024)
Tri Jaya Sentosa is a marketing distributor for Frisian Flag dairy products. CV XYZ is located at Ds. Mojodeso, District. Cotton, Bojonegoro Regency. CV. Tri Jaya itself also often experiences a problem called the Bullwhip Effect in certain products. Demand from consumers often changes, so that sometimes it is difficult for companies to predict consumer demand, this situation often results in an increase or decrease in demand from consumers for a product. For this reason, an approach using Supply Chain Management (SCM) is needed. To overcome the problems that occur at CV. XYZ above, the author tries to provide a calculation solution to calculate, reduce and find out what causes the Bullwhip Effect. CV XYZ priorities for retail tend to experience a bullwhip effect. This situation ensures that product distribution is not constrained. CV XYZ priority is Tiga Bersaudara retail for BKM Sachet products because the bullwhip effect value is quite high, namely 2,825. This can mean that information distortion occurs so that information data from retail to sub-distributors does not run smoothly.